2001
DOI: 10.1097/00003246-200106000-00037
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic scheme and effect of “extended sigh” as a recruitment maneuver in patients with acute respiratory distress syndrome: A preliminary study

Abstract: We present a new form of sigh (i.e., extended sigh) capable of achieving an augmented recruiting pressure x time through a prolonged inflation on a gradually increased end-expiratory pressure. In view of the sustained effect and absence of major complications in our patients, extended sigh could be a useful recruitment maneuver in acute respiratory distress syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
1
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 32 publications
4
61
1
2
Order By: Relevance
“…In all studies using single or repeated recruitment manoeuvres that showed an increase in P a O 2 the effect was immediate but usually only short lasting [57][58][59][60][61][62][63][64][65][66][67][68]. Only one study on patients receiving mechanical ventilation for less than 72 h showed a prolonged oxygen increase of 60% in 4 h after a single sustained inflation [69].…”
Section: Human Studiesmentioning
confidence: 99%
“…In all studies using single or repeated recruitment manoeuvres that showed an increase in P a O 2 the effect was immediate but usually only short lasting [57][58][59][60][61][62][63][64][65][66][67][68]. Only one study on patients receiving mechanical ventilation for less than 72 h showed a prolonged oxygen increase of 60% in 4 h after a single sustained inflation [69].…”
Section: Human Studiesmentioning
confidence: 99%
“…Because the mechanism of hypercarbia in this setting may be an increase in V D /V T , it is possible that monitoring of end-tidal CO 2 alone may be insufficient. Safety of the maneuver may be further enhanced by utilizing regular recovery periods at lower pressures (as utilized by Borges et al 11 ), utilizing lower airway pressures for shorter durations, 13,26 or by use of a larger driving pressure (peak inspiratory pressure minus PEEP) during the maneuver. The use of esophageal pressure monitoring to quantify transpulmonary pressure 27 may also enhance the safety profile of SRS.…”
Section: Discussionmentioning
confidence: 99%
“…Performing recruitment manoeuvres is a strategy that aims at briefly increasing the plateau pressure above 30 cmH 2 O in order to overcome the critical opening pressures of the lung units. There are different methods to recruit the lung, as sighs [26], sustained inflation [27], extended-sighs [28]. After the recruitment manoeuvre, a sufficient amount of PEEP should be set to maintain the recruitment.…”
Section: Recruitment Manoeuvresmentioning
confidence: 99%